Hot work die steel material with high thermal conductivity and preparation method thereof

By optimizing the composition and heat treatment process of the hot-working mold steel material, combined with the accompanying waterway mold technology, the problem of low thermal conductivity of existing hot-working mold steel materials is solved, high thermal conductivity and mold temperature balance is achieved, and mold life is extended. And improves production efficiency.

CN119433368APending Publication Date: 2025-02-14NINGBO CHUANGXIN RAPID PROTOTYPING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411700096.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The thermal conductivity of existing thermal work mold steel materials is low, which makes it difficult for the mold to achieve uniform cooling in high-temperature and high-pressure environments, and is prone to thermal cracking and cracking, affecting product quality.

Method used

By optimizing the chemical composition and heat treatment process of the thermal work mold steel material, a new thermal work mold steel material with high thermal conductivity was prepared, and combined with the accompanying waterway mold technology, the thermal conductivity of the thermal node insert is improved to realize the mold of the entire set of molds Temperature balance.

Benefits of technology

It improves the thermal conductivity of the steel material of the hot-working mold, extends the life of the mold, improves the production rhythm, and ensures uniform cooling of the mold and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433368A_ABST
    Figure CN119433368A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of additive manufacturing, and particularly discloses a hot work die steel material with high thermal conductivity and a preparation method of the hot work die steel material. 0 to 1.5 percent of Cr; 2.5 to 3.4 percent of Mo; 0.4 to 0.9 percent of V; 0 to 0.9% of Si; 0.7 to 1.1% of Mn; and the balance of Fe and inevitable impurities. The service life of the die-casting die is prolonged, the production takt time of the die-casting die is prolonged, combination of a carbon steel type hot work die steel material and the shape follow-up waterway die is achieved, the heat conduction capacity of the hot node insert is further improved, and die temperature balance of the whole set of die is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a hot working die steel material with high thermal conductivity and a preparation method thereof. Background Art

[0002] The high temperature and high pressure environment in die-casting production places high demands on the mold. In addition, in order to adapt to the large-scale die-casting machines with increasingly large formats and clamping pressures being put into the production of new energy vehicle body structural parts, the temperature of the liquid metal injected into the cavity will be higher than 700°C, and the injection speed will be faster, which will further increase the temperature difference between the high and low points of the entire mold, especially at the hot nodes and the gates. The problem of excessive mold temperature needs to be solved urgently. The water channels in subtractive manufacturing are mostly straight-hole water channels, which provide limited cooling effect for the mold. Improving the thermal conductivity of the die-casting mold material itself is an effective way to further improve the cooling uniformity of the entire mold and speed up the production cycle.

[0003] At present, in order to increase the cooling speed of high-temperature positions such as hot nodes and sprues in the entire mold and improve the cooling uniformity of the entire mold, mold inserts with additively manufactured conformal water channels will be used. Because the rapid cooling and heating characteristics of additive manufacturing (SLM, Laser Cladding, etc.) technology are consistent with the quenching process of traditional hot working die steel (TQ1, Dievar, H13, H11, etc.), martensitic aging steel (18Ni300, CX, etc.) is often used as the metal powder raw material for additive manufacturing die-casting molds. The biggest problem is the low thermal conductivity value, which is only 2 / 3 of that of traditional steel. It is necessary to combine metal powder materials with fast heat conduction performance and additive manufacturing conformal water channel mold technology to provide more efficient molds for die-casting production.

[0004] Carbon steel hot working die steel represented by Dievar and H13 has low thermal conductivity. The die-casting production of large-size structural products requires rapid condensation of liquid metal at higher temperatures for near-net forming. Current die steel materials are prone to high die surface temperatures during production due to low heat conduction rates. After the release agent is sprayed, the surface cools rapidly, causing thermal cracking and cracking on the die surface during moderate use, which in turn affects product quality.

[0005] The additive manufacturing of traditional hot working die steel is very difficult. It depends on the heating temperature of the substrate. Only in a small experimental device can a small area be heated to more than 200°C. In the actual production process, it is difficult for the equipment to heat more than 200°C. This also leads to large welding stress in the rapid melting and solidification process of traditional hot working die steel powder in additive manufacturing, which in turn leads to cracking of the material. It is difficult to combine the high thermal conductivity of the material itself with the rapid heat conduction method of the conformal waterway. No solution has been proposed for related technical issues. Summary of the invention

[0006] In view of the problems in the related technology, the present invention proposes a hot working die steel material with high thermal conductivity and a preparation method thereof to overcome the above-mentioned technical problems existing in the existing related technology. The purpose of the present invention is to improve the life and production cycle of the die-casting mold, realize the combination of carbon steel hot working die steel material and conformal water channel mold, further improve the thermal conductivity of the hot node insert, and achieve mold temperature balance of the whole set of molds.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A hot working die steel material with high thermal conductivity, the chemical composition of which is as follows in weight percentage:

[0009] C: 0.3~0.35%;

[0010] Cr: 0-1.5%;

[0011] Mo: 2.5-3.4%;

[0012] V: 0.4~0.9%;

[0013] Si: 0-0.9%;

[0014] Mn: 0.7-1.1%;

[0015] The balance is Fe and inevitable impurities.

[0016] Preferably, its chemical composition is as follows in weight percentage:

[0017] C: 0.32%;

[0018] Cr: 0.5%;

[0019] Mo: 2.8%;

[0020] V: 0.8%;

[0021] Si: 0.9%;

[0022] Mn: 0.9%;

[0023] The balance is Fe and inevitable impurities.

[0024] Preferably, its chemical composition is as follows in weight percentage:

[0025] C: 0.34%;

[0026] Cr: 1.5%;

[0027] Mo: 3.4%;

[0028] V: 0.6%;

[0029] Si: 0.9%;

[0030] Mn: 0.9%;

[0031] The balance is Fe and inevitable impurities.

[0032] Preferably, its chemical composition is as follows in weight percentage:

[0033] C: 0.31%;

[0034] Cr: 1.2%;

[0035] Mo: 2.7%;

[0036] V: 0.5%;

[0037] Si: 0.3%;

[0038] Mn: 0.8%;

[0039] The balance is Fe and inevitable impurities.

[0040] Preferably, the hot working die steel material is spherical powder, and the powder particle size range is 15 to 53 um.

[0041] To achieve the above object, the present invention also provides the following technical solutions:

[0042] A method for preparing a hot working die steel material with high thermal conductivity comprises the following steps:

[0043] Step 1: Pre-prepare the hot working die steel material into spherical powder by vacuum gas atomization, wherein the powder particle size range of the additive manufacturing state is 15-53um;

[0044] Step 2: Use the selective laser melting equipment and optimize the SLM molding parameters to prepare the processing samples;

[0045] Step 3: Heat treat and cool the prepared processed samples to obtain optimal material properties.

[0046] A hot working die steel material with high thermal conductivity and a preparation method thereof, wherein the optimized SLM forming parameters include: a laser power of 280W, a line scanning speed of 980mm / s, a layer thickness of 50μm, and a line spacing of 0.05mm.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) The present invention is a hot working die steel material with high thermal conductivity and a preparation method thereof. By optimizing the composition and heat treatment control, a new type of hot working die steel with high thermal conductivity under the best composition and process is selected, and the thermal conductivity and mechanical properties at different temperatures are tested to determine the feasibility of this material in die casting production. This hot working die steel material can be used at the die end, and its performance is better than that of traditional hot working die steel materials, which can further improve the life and production cycle of the die casting die;

[0049] (2) The present invention relates to a hot working die steel material with high thermal conductivity and a preparation method thereof. A gas atomization powder making process is performed on a new type of high thermal conductivity hot working die steel material, a suitable powder particle size range under the additive manufacturing process is screened, additive molding is performed on the material, the molding process is regulated, the additive manufacturing process under the optimal mechanical property state is selected, and the heat treatment process is regulated. The feasibility of additive manufacturing of the hot working die steel material with high thermal conductivity is evaluated, and the actual technical route for additive manufacturing of conformal water channel high thermal conductivity molds is determined. At the same time, the material is gas atomized and powdered to adapt to the additive manufacturing process, and the carbon steel hot working die steel material and the conformal water channel mold are combined, the thermal conductivity of the hot node insert is further improved, and the mold temperature balance of the entire mold is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is a schematic flow chart of the method for preparing the hot working die steel material of the present invention;

[0051] Figure 2 This is a comparison chart of thermal conductivity tests of the hot working die steel material of the present invention;

[0052] Figure 3 This is a chemical composition diagram of the hot working die steel material of the present invention. DETAILED DESCRIPTION

[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] The present invention makes appropriate changes to the ingredients based on commercial H13, appropriately reduces the carbon content, increases the temperature of the austenite stable zone, makes the matrix martensite transformation more thorough, and reduces the amount of carbon dissolved in the matrix, reduces the matrix hardness, and reduces the risk of quenching cracking. The Cr content is reduced to prevent the generation and coarsening of M23C6 carbides during the tempering process and service process, which leads to a decrease in material performance; the manganese content is appropriately increased to improve the hardenability of steel; the molybdenum content is increased to improve the high-temperature performance of steel and the overall red hardness of the material. On the whole, the priority of molybdenum and vanadium elements to combine with carbon to form carbides is increased, the types of elements in steel and the content of other elements except iron are reduced, the purity of the matrix after the tempered carbides are precipitated is increased, and the thermal conductivity of the material is improved. The following Table 1 is a comparison of material thermal conductivity tests.

[0055] Table 1 Comparison of thermal conductivity tests of materials

[0056]

[0057] After smelting and spheroidizing annealing process, impurities on the steel surface are removed, and quenching oil is used as the quenching medium of the steel for quenching to avoid quenching cracking and ensure quenching uniformity. The quenching temperature is set to 980℃, which is higher than the AC3 temperature point calculated by the material, to ensure oil quenching cooling after full austenitization. The holding time of the highest temperature section of the steel is appropriately increased or decreased according to the size. Multiple tempering processes are used to reduce the hardness of the martensitic matrix in the quenched state and reduce the quenching stress, so that the material can achieve a reasonable combination of strength and plasticity, which is convenient for processing and use in the mold end. As shown in Table 1, it is a combination of quenching and tempering processes under different sizes. Table 2 below shows the quenching and tempering processes of materials of different sizes.

[0058] Table 2 Quenching and tempering process of materials of different sizes

[0059]

[0060] The SEM metallographic structure of sample No. 3 was taken as the object. The results showed that martensite was the main structure, the carbide size was less than 1μm, and the distribution was relatively uniform. According to the EDS scanning results of the elements, the carbides were determined to be Mo and V-enriched M6C and MC-type carbides, and no M23C6-type carbides appeared, indicating that the composite material composition was set as expected, and the material would have good performance in tempering resistance and high temperature resistance. The thermal conductivity values ​​of the test materials at different temperatures were compared with those of the traditional hot working die steel H13, which were significantly higher than H13, such as Figure 2 shown.

[0061] The material was atomized and pulverized, and the powder with a particle size of 15-53 μm was screened for selective laser melting (SLM) molding. The laser power was 280 w, the scanning speed was 980 mm / s, the layer thickness was 50 μm, and the line spacing was 0.05 mm. The thermal conductivity, tensile properties and impact properties of the powder molding material were tested, and quenching and tempering treatments were carried out according to the block material heat treatment system before pulverization treatment to reduce the accumulated stress of additive manufacturing and improve the toughness of the material. The results are shown in Table 3.

[0062] Table 3 Mechanical properties of materials for additive manufacturing

[0063]

[0064]

[0065] Example 1

[0066] The present invention discloses a hot working die steel material with high thermal conductivity, and its chemical composition is as follows in weight percentage:

[0067] C: 0.32%;

[0068] Cr: 0.5%;

[0069] Mo: 2.8%;

[0070] V: 0.8%;

[0071] Si: 0.9%;

[0072] Mn: 0.9%;

[0073] The balance is Fe and inevitable impurities.

[0074] Example 2

[0075] The present invention discloses a hot working die steel material with high thermal conductivity, and its chemical composition is as follows in weight percentage:

[0076] C: 0.34%;

[0077] Cr: 1.5%;

[0078] Mo: 3.4%;

[0079] V: 0.6%;

[0080] Si: 0.9%;

[0081] Mn: 0.9%;

[0082] The balance is Fe and inevitable impurities.

[0083] Example 3

[0084] The present invention discloses a hot working die steel material with high thermal conductivity, and its chemical composition is as follows in weight percentage:

[0085] C: 0.31%;

[0086] Cr: 1.2%;

[0087] Mo: 2.7%;

[0088] V: 0.5%;

[0089] Si: 0.3%;

[0090] Mn: 0.8%;

[0091] The balance is Fe and inevitable impurities.

[0092] In addition, with the aid of the above technical solution, on the basis of the first, second and third embodiments, the hot working die steel material is a spherical powder, and the powder particle size range is 15 to 53 um.

[0093] Example 4

[0094] To achieve the above object, the present invention also provides the following technical solutions:

[0095] A method for preparing a hot working die steel material with high thermal conductivity comprises the following steps:

[0096] Step 1: Pre-prepare the hot working die steel material into spherical powder by vacuum gas atomization, wherein the powder particle size range of the additive manufacturing state is 15-53um;

[0097] Step 2: Use the selective laser melting equipment and optimize the SLM molding parameters to prepare the processing samples;

[0098] Step 3: Heat treat and cool the prepared processed samples to obtain optimal material properties.

[0099] The optimized SLM forming parameters include: laser power of 280w, line scanning speed of 980mm / s, layer thickness of 50μm, and line spacing of 0.05mm.

[0100] In summary, with the help of the above technical solution of the present invention, the following effects can be achieved:

[0101] By optimizing the composition and heat treatment control, a new type of hot working die steel with high thermal conductivity under the best composition and process is selected, and the thermal conductivity and mechanical properties at different temperatures are tested to determine the feasibility of this material in die casting production. This hot working die steel material can be used at the die end, and its performance is better than that of traditional hot working die steel materials, which can further improve the life and production cycle of die casting molds;

[0102] The atomization powder making process is carried out on the new high-temperature hot working die steel material, the suitable powder particle size range under the additive manufacturing process is screened, the powder is additively formed, the forming process is regulated, the additive manufacturing process under the optimal mechanical properties is selected, and the heat treatment process is regulated. The feasibility of additive manufacturing of hot working die steel materials with high thermal conductivity is evaluated, and the actual technical route for additive manufacturing of conformal water channel high thermal conductivity molds is determined. At the same time, the material is atomized and powdered to adapt to the additive manufacturing process, and the combination of carbon steel hot working die steel materials and conformal water channel molds is realized, which further improves the thermal conductivity of the hot node inserts and achieves mold temperature balance of the entire mold.

[0103] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A hot working die steel material with high thermal conductivity, characterized in that: Its chemical composition in weight percentage is as follows: C:0.3~0.35%; Cr:0~1.5%; Mo: 2.5-3.4%; V:0.4~0.9%; Si: 0-0.9%; Mn: 0.7-1.1%; The balance is Fe and inevitable impurities.

2. The hot working die steel material with high thermal conductivity according to claim 1, characterized in that: Its chemical composition in weight percentage is as follows: C:0.32%; Cr:0.5%; Mo: 2.8%; V:0.8%; Si: 0.9%; Mn: 0.9%; The balance is Fe and inevitable impurities.

3. The hot working die steel material with high thermal conductivity according to claim 1, characterized in that: Its chemical composition in weight percentage is as follows: C:0.34%; Cr:1.5%; Mo: 3.4%; V:0.6%; Si: 0.9%; Mn: 0.9%; The balance is Fe and inevitable impurities.

4. The hot working die steel material with high thermal conductivity according to claim 1, characterized in that: Its chemical composition in weight percentage is as follows: C:0.31%; Cr:1.2%; Mo: 2.7%; V:0.5%; Si: 0.3%; Mn: 0.8%; The balance is Fe and inevitable impurities.

5. A hot working die steel material with high thermal conductivity according to claim 2, 3 or 4, characterized in that: The hot working die steel material is spherical powder, and the powder particle size range is 15 to 53 um.

6. A method for preparing a hot working die steel material with high thermal conductivity, used for the method for preparing a hot working die steel material with high thermal conductivity as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Pre-prepare the hot working die steel material into spherical powder by vacuum gas atomization, wherein the powder particle size range of the additive manufacturing state is 15-53um; Step 2: Use the selective laser melting equipment and optimize the SLM molding parameters to prepare the processing samples; Step 3: Heat treat and cool the prepared processed samples to obtain optimal material properties.

7. The method for preparing a hot working die steel material with high thermal conductivity according to claim 6, characterized in that: The optimized SLM molding parameters include: laser power of 280W, line scanning speed of 980mm / s, layer thickness of 50μm, and line spacing of 0.05mm.